Pengaruh Profitabilitas, Likuditas dan Ukuran Perusahaan Terhadap Peringkat Obligasi Pada Perusahaan LQ 45 - ni'mah, nadlirotun; Widodo, Agustina (Bisnis-Net, 2024)
One  form of funding that can be done by a company is by issuing bonds. The purpose of this study is to evaluate and clarify the impact on profitability, liquidity and company size on the bond ratings of LQ 45 companies which are rated by PT Pefindo which is listed on the Indonesia Stock Exchange. The type of data used is secondary data from 45 companies that have the best shares and are most popular with investors. This data was collected from the official website of the Indonesian Stock Exchange, www.Idx. Co.id and PT. Pefindo. The sampling method uses purposive sampling. This research uses eleven LQ 45 companies that issue bonds and have been ranked by PT Pefindo from 2018 to 2022. The data analysis method used is a logistic regression analysis test using the IBM SPSS 25 statistical program. The results of the research show that profitability has a significant negative effect on bond ratings, liquidity has a positive and insignificant effect on bond ratings and company size has a positive and insignificant effect on bond ratings in LQ companies. 45 listed on the Indonesian Stock Exchange.  Keywords: Profitability, Liquidity, Company Size and bond rating.